Amomum bungoensis: A New Species of Amomum (Zingiberaceae) from Sarawak, Malaysia - Aimi Syazana, Sedek; Qammil Muzzammil, Abdullah@Meekiong B. Kalu; Nur Afifah, Ismail; Syauqina Syasya, Mohd Yusoff (Hindawi Publishing, 2018)
A new species of Amomum Roxb. from Sarawak is described. Amomum bungoensis S. Aimi Syazana & Meekiong, sp. nov., shows similarity with A. durum S. Sakai and Nagamasu by having similar fruit characteristics but differs in labellum and anther crest of the flowers. Detailed description and photographs are provided.